Tajikistan’s Higher Education System in Transformation - Wetzinger, Johannes (International Higher Education, 2024)
<h3 id="since-the-dissolution-of-the-soviet-union-in-1991-the-transformation-of-tajikistans-higher-education-system-has-been-characterized-by-institutional-expansion-and-growing-enrollment-moreover-tajikistan-has-taken-steps-to-align-with-some-trends-in-the-european-higher-education-area-despite-the-absence-of-a-membership-perspective-however-difficulties-regarding-employability-of-graduates-and-outmigration-of-young-people-pose-important-obstacles-for-the-future-of-the-state-controlled-higher-education-system" data-pm-slice="1 1 []">Since the dissolution of the Soviet Union in 1991, the transformation of Tajikistan’s higher education system has been characterized by institutional expansion and growing enrollment. Moreover, Tajikistan has taken steps to align with some trends in the European Higher Education Area, despite the absence of a membership perspective. However, difficulties regarding employability of graduates and outmigration of young people pose important obstacles for the future of the state-controlled higher education system.​